Targeting Amino Acid Metabolic Vulnerabilities in Myeloid Malignancies - Fultang, Livingstone; Gneo, Luciana; De Santo, Carmela; Mussai, Francis J. (Frontiers in Oncology, 2021)
Tumor cells require a higher supply of nutrients for growth and proliferation than normal cells. It is well established that metabolic reprograming in cancers for increased nutrient supply exposes a host of targetable vulnerabilities. In this article we review the documented changes in expression patterns of amino acid metabolic enzymes and transporters in myeloid malignancies and the growing list of small molecules and therapeutic strategies used to disrupt amino acid metabolic circuits within the cell. Pharmacological inhibition of amino acid metabolism is effective in inducing cell death in leukemic stem cells and primary blasts; as well as reducing tumor burden in vivo murine models of human disease. Thus targeting amino acid metabolism provides a host of potential translational opportunities for exploitation to improve the outcomes for patients with myeloid malignancies.